2002
DOI: 10.2225/vol5-issue3-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin production by root cultures of Plumbago rosea

Abstract: Root cultures of Plumbago rosea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Effect of cytokinins in combination with NAA on rooting depends on kind and concentration of cytokinin. Panichayupakaranant and Tewtrakul (2002) reported that the combination of NAA and Kn was found to be best for root growth in P. rosea. However, in the present study, the combination of NAA and Kn was not suitable for increasing the rooting percentage.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of cytokinins in combination with NAA on rooting depends on kind and concentration of cytokinin. Panichayupakaranant and Tewtrakul (2002) reported that the combination of NAA and Kn was found to be best for root growth in P. rosea. However, in the present study, the combination of NAA and Kn was not suitable for increasing the rooting percentage.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (Paiva unplublished data) showed that, in P. scandens, this naphthoquinone is found predominantly on the roots, with low concentrations in aerial parts. In other species of the genus Plumbago, such as P. rosea, the literature data also point to the accumulation of plumbagin in roots (Panichayupakaranant and Tewtrakul 2002). A study carried out by Verma et al 2002, revealed the potentialities of the hairy root cultures of P. zeylanica for the production of plumbagin.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the low germination of seeds and death of young plantlets under natural environment makes conventional propagation of the plant challenging and inadequate to meet the growing demand of the pharmaceutical companies. Various in vitro protocols have been used in an effort to boost plumbagin production in Plumbago species including the induction of adventitious roots in P. indica (Panichayupakaranant and Tewtrakul 2002) and P. zeylanica (Sivanesan and Jeong 2009). …”
Section: Introductionmentioning
confidence: 99%